Pengaruh Model Pembelajaran Children Learning In Science (CLIS) Terhadap Hasil Belajar Tematik Siswa Kelas IV di SD Negeri 0104 Sibuhuan - Era Mutiah; Miftah Hurrohmah Hasibuan; Rani Astria Silvera Harahap (Yayasan Perguruan Kampus, 2025)
The aim of this research is to find out: (1) what are the thematic learning outcomes of class IV students at SD Negeri 0104 Sibuhuan. (2) what is the influence of the children learning in science (CLIS) learning model on the thematic learning outcomes of class IV students at SD Negeri 0104 Sibuhuan. This research uses a quantitative approach. The data collection techniques used are observation and tests. The sample in this study was 30 students, or the total population consisting of 10 men and 20 women with information evaluation strategies the use of normality checks, homogeneity tests, and speculation assessments. based totally at the effects of studies executed by researchers, it can be concluded that (1) The learning outcomes of students IV at SD Negeri 0104 Sibuhuan during the pre-test were obtained on average at 57.7 and after being treated with the children learning in science learning model (CLIS) obtained an average post-test score of 84.1. From these results, a significant increase can be seen. (2) The outcomes of hypothesis trying out the use of the t check show that the T price is 2.17 while compared with T desk at a significance degree of 5% or 0.05 with stages of freedom (dk) = 28 that's 1.70. primarily based on those facts, Tcount is extra than Ttable or (2.17 > 1.70), so Ha is everyday and Ho is rejected. So it may be concluded that there is a sizable have an impact on between the children learning in science (CLIS) learning model on the thematic learning outcomes of class IV students at SD Negeri 0104 Sibuhuan.